SYNTHESIS OF ADSORBENT MAGNETITE SILICA FUNCTIONALIZED CETYLTRIMETHYLAMMONIUM BROMIDE (CTAB) FROM IRON SAND KLAYAR BEACH PACITAN - Endang Sawitri; Choiril Azmiyawati; P Siahaan; Adi Darmawan (Jurnal Sains Dasar, 2018)
Synthesis of Magnetite Silica cetyltrimethylammonium bromide (magsil-CTAB) had been successfully performed using iron sand Klayar beach as a source of natural magnetite, sodium silicate, HCl, and cetyltrimethylammonium bromide (CTAB). Addition of CTAB on silica magnetite was expected to improve the ability of the adsorbent to adsorb polar compounds such as phenols. Synthesis began with the separation of the magnetite from iron sands by separation magnetically done using permanent magnets. Silica coating on magnetite done via sol-gel method with a ratio 1:20 of magnetite and sodium silicate followed by addition of HCl to form a gel. Gel was dried at a temperature of 80 0C and 350 °C for calcination. Results obtained soaked with CTAB solution with a concentration of 0.5 mM; 1 mM; 2 mM and stirred for 24 hours. Binding of silica and magnetite above the CTAB tested by Fourier Transform Infra Red (FTIR). The presence of silica in magnetite indicated by the appearance of spectra at wave number 900 and 3500-3200 cm-1 indicating the presence of a hydroxyl group of silanol and water molecules. Besides the presence of two strong peaks observed around 1100 and 800 cm-1, respectively show the Si-O-Si asymmetric stretching and bending. From the results of spectra could be seen further there were difference intensity of the main peaks for different samples used, especially on the area around 2300 cm-1 to be a group of nitrile (C-N) and about 3700-3500 cm-1 due to the amide (N-H) of the CTAB as expected. Keywords: magnetite, silica, sol-gel, coating, CTAB